ANALYZING THE USE OF DIFFERENT SOCIAL MEDIA MARKETING TECHNIQUES APPLIED BY DARK TOURISM SPOTS TO ATTRACT THE ATTENTION OF DARK TOURISTS: A STUDY ON DIFFERENT SOCIAL MEDIA MARKETING TECHNIQUES OF BANGABANDHU MEMORIAL MUSEUM IN DHAKA - Molla, Mijanur Rahman; Lima, Fahima Sultana; Tareq, Sk. Md. Hassan (American International Journal of Multidisciplinary Scientific Research, 2022)
Nowadays, people rely on social media for advertisements, news, information tourist places promotion, especially on Facebook. For this reason, Bangabandhu memorial museum uses social media marketing techniques to attract tourist attention. Social media marketing can increase tourists and share different information types important for any tourist place. At present, people make a tour by knowing about the site through social media. So, the researcher insists that social media marketing techniques are more effective for Bangabandhu memorial museum. This paper has five steps: the first steps of this project paper have introduction, methodology and literature review. The second step has formatted the conceptual framework. The third steps of this project have some objectives that identified by the researcher that which used for attracting dark tourists for Bangabandhu memorial museum, analyzing the uses of social media marketing for attracting dark tourists which collected from questionnaire survey that was operated by a huge number of executive & employee of Bangabandhu memorial museum and face-to-face interview with the tourists. And the fourth steps show the significant findings of the research paper. The last steps of the project paper are recommending some guidelines for Bangabandhu memorial museum and further research. By this research, researchers identify the uses of Facebook marketing for attracting dark tourists by Bangabandhu memorial museum. Because nowadays, people are more familiar with Facebook and have more potential to promote dark tourism spots through social media. If Bangabandhu memorial museum properly uses Facebook marketing, they can increase tourists. So, promoting these dark tourism spots on Facebook is the most popular social media platform technique. So, Facebook media can increase dark tourists for Bangabandhu memorial museum. JEL Classification Codes: M31.